We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive pseudonymised information about your use of our website. cookie policy and privacy policy.
 
+0  
 
0
271
1
avatar

Solve for x

2x-6 = 3(10-2x)/2 + (3+5x)/2

 

I dont get it

 Oct 9, 2017
 #1
avatar+2338 
0

In order to solve for x in this equation, we must perform a multitude of operations.

 

\(2x-6=\frac{3(10-2x)}{2}+\frac{3+5x}{2}\) Multiply by 2 on both sides to eliminate the pesky fractions.
\(4x-12=3(10-2x)+3+5x\) Distribute the 3 into the term 10-2x.
\(4x-12=30-6x+3+5x\) Simplify the right hand side by combining the like terms.
\(4x-12=-x+33\) Add x to both sides to get the x's on one side of the equation.
\(5x-12=33\) Add 12 to both sides.
\(5x=45\) Divide by 5 on both sides of the equation.
\(x=9\)  
   
 Oct 9, 2017

25 Online Users

avatar